A Possible Pedigree and Other Notes on a 14th Century Blanc Tournois - Bontas, Andrei (KOINON: The International Journal of Classical Numismatic Studies, 2021)
In November 2016, a well known Parisian auction house offered an interesting billon blanc au châtel fleurdelisé, struck for Robert de Bar, a Scarponnois count and margrave and the first Duke of Bar (c. 1352/1355-1411). Placed between the Kingdom of France and the Holy Roman Empire, pays Barrois entered the Royal overlordship of Philippe IV in 1301, following a failed attempt by Henry III de Bar to gain practical independence and an effective emancipation for the whole of Barrois mouvant by joining Edward I Plantagenent’s side in his conflict against France in the late 1290s. At the eastern margins of a France caught up in the Capetian-Plantagenet Hundred Years War, pays Barrois was still important enough for King Jean II of France to bestow its contemporary ruler, Count and Margrave Robert, with the title of Duke and raise his importance possibly to the stature of Peer of the France, while the Margraviate of Pont-a-Mousson gave him a voice in the Imperial Diet (1354). The coinage of the Counts and Dukes of Bar was of interest to antiquarians, historians and numismatists at least as early as the 19th century and was explored at length by numismatist, historian, archaeologist and all-in-all polymath and Renaissance man Felicien de Saulcy in his monographic study of the monnoie de pays Barrois—Recherches sur les monnaies des comtes et ducs de Bar of 1843. Written almost 180 years ago, de Saulcy’s work influenced other mid 19th century researchers and antiquarians, like Poey d’Avant (who cites him extensively, although not on the issue of pays Barrois and not only to agree with him), and was relevant and comprehensive enough to influence M. L. Maxe-Werly and D. Flon in their respective studies.